(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The banking sector is a genuine financial service industry that is responsible for an economy’seconomic progress. Customer satisfaction is critical for maintaining current customers and acquiring newconsumers to expand the company’s operations. Day by day, a fierce rivalry is expanding across thecorporate sector. Customer happiness is critical to a company’s long-term performance and the studywhich mainly discussed about overview of the Indian banking industry, History of banking in India,General banking scenario in India, Types of banks, Evolution of banking industry, It in banking.